Penentuan Rute Terpendek Di Kantor Pos Kabupaten Blitar Dalam Pendistribusian Paket Menggunakan Algoritma Clarke And Wright Savings - Puji Wianto, Wildan Faried Anshoriy; Juhari, Juhari; Nasichuddin, Achmad (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
Marketing strategy is a very important part in the execution of the overall corporate strategy, especially in a very tight competitor state. Route is a very important aspect considered by goods distribution companies. An effective and efficient distribution process is one of the factors whose conditions begin to align with other indicators in an effort to achieve customer satisfaction. The strategy that can be done is to involve calculating algorithms in contributing systematic and measurable solutions. The Clarke and Wright Savings algorithm is an effective method in determining the shortest route of distributing goods, because the Clarke and Wright Savings method has its own heuristics which make savings in the form of mileage or distribution time. This study aims to determine the shortest route at the Blitar checkpoint post office (KPRK) in distributing express service type bags to each branch post office point (KPC) using the Clarke and Wright Savings Algorithm. The results of the discussion on the application of the Clarke and Wright Savings method to determine the shortest route for the service bag distribution fleet from the KPRK Blitar post office to KPC can be concluded that, there are two initial routes owned by the company with a total delivery distance of 189.7 km. After calculation, two routes with the shortest distance will be traveled with a total delivery distance of 171 km. Route group 1 is Blitar Post Office à KPC Garum à KPC Nglegokà KPC Gandusarià KPC Talun KPC Wlingi à KPC Doko à KPC Kesamben à KPC Selopuroà KPC Binangun à KPC Kanigoro à KPC Lodoyo à KPC Kademangan à Post Office with a distance of 116.7 km. As for route 2, namely the blitar post office à KPC Sanan Kulon à KPC Ponggok à KPC Srengat à KPC Kademangan à KPC Udanawu à Blitar post office with a distance of 54.3 km. With the establishment of routes with the closest distance, the company can save mileage by 9.85%.